2020
DOI: 10.1101/2020.04.29.066332
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Single-cell analysis uncovers mechanisms of plasticity in leukemia initiating cells

Abstract: Leukemia initiating cells (LICs) fuel leukemic growth and spark relapse. Previously thought to be primitive and rare, the LIC state may actually be heterogeneous and dynamic, enabling evasion of therapies. Here, we use single-cell transcriptomics to dissect the ontogeny of MLL-rearranged B-lymphoblastic leukemia (MLL-r B-ALL).Although we identify rare transcriptionally and phenotypically primitive LICs, we also observe LICs emerging from more differentiated populations with the capability to replenish the full… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…3A). Prior studies have shown that treatment resistant B-ALL xenografts and high risk diagnosis-or relapse-B-ALL patient samples express hematopoietic stem cell (HSC) genes and undergo metabolic rewiring that is linked to a stress-tolerant state (7,(23)(24)(25). We found similar upregulation of HSC-as well as acute myeloid leukemia (AML) stem cell (LSC)-gene sets in CNS blasts (Fig.…”
Section: Cns Disseminated Blasts Transcriptionally and Phenotypically Resemble Therapy-resistant Cellsmentioning
confidence: 52%
See 1 more Smart Citation
“…3A). Prior studies have shown that treatment resistant B-ALL xenografts and high risk diagnosis-or relapse-B-ALL patient samples express hematopoietic stem cell (HSC) genes and undergo metabolic rewiring that is linked to a stress-tolerant state (7,(23)(24)(25). We found similar upregulation of HSC-as well as acute myeloid leukemia (AML) stem cell (LSC)-gene sets in CNS blasts (Fig.…”
Section: Cns Disseminated Blasts Transcriptionally and Phenotypically Resemble Therapy-resistant Cellsmentioning
confidence: 52%
“…This suggests that CNS blasts have extra mitochondrial reserve capacity available in order to produce more energy or mitochondrial ROS if needed. Overall, CNS blasts have a transcriptional profile and metabolic phenotype that resembles chemotherapyresistant subclones and this converges on a stress-tolerant state (7,(23)(24)(25). Although our study focused on a static analysis of blasts present in the CNS and was not designed to investigate whether these distinct functional properties specifically impact on the trafficking, survival or growth of blasts in the leptomeningeal space, our data argues that improving treatment of CNS disease will require targeting of molecular pathways driving these essential processes.…”
Section: Cns Disseminated Blasts Transcriptionally and Phenotypically Resemble Therapy-resistant Cellsmentioning
confidence: 99%
“…Recent work using single-cell RNA-sequencing has garnered considerable novel insight into normal and aberrant hematopoiesis, cell-cell interactions, characterization of bone marrow and immune (non-clonal) cells as well as tissue stroma and leukemia-initiating cells. [33][34][35][36] This technology enables detection and characterization of intratumor heterogeneity and provides much needed granularity to key issues, including acquisition of individual or specific combinations of somatic mutations or proteins expressed by cellular subtypes and mechanisms of relapse or treatment resistance. As an illustration, the use of single-cell-level sequencing in a study of MF, conducted by Psaila and colleagues, revealed megakaryocyte-biased hematopoiesis with megakaryocyte progenitors demonstrating distinct inflammatory and metabolic signatures, and increased expression of the surface antigen G6B (MPIG6B) on MF stem cells and progenitors (Figure 4).…”
Section: Intratumoral Heterogeneitymentioning
confidence: 99%